A Trusted Open Platform - England, Paul; Lampson, Butler; Manferdelli, John; Peinado, Marcus; Willman, Bryan (IEEE Computer, 2003)
Microsoft’s next-generation secure computing base extends personal computers to offer mechanisms that let high-assurance software protect itself from the operating systems, device drivers, BIOS, and other software running on the same machine.